Divided-Pulse Nonlinear Amplification at 1.5 μm - Qiang Hao; Yunfeng Wang; Tingting Liu; Hong Hu; Heping Zeng (IEEE Photonics Journal, 2016)
Divided-pulse nonlinear amplification was developed in the anomalous dispersion regime by combining the concepts of divided-pulse nonlinear amplification and divided-pulse compression. We realized compressor-free ultrafast pulse amplifiers at 1.5 μm with the help of simultaneous pulse amplification and compression in single-mode and few-mode fibers with anomalous dispersion. With optimized positive prechirping on the seed pulse, the interplay between the dispersive and nonlinear effects was controlled to get transform-limited soliton replicas. Experiments, as well as numerical simulations, demonstrated that ∼0.75 nJ per replica was the optimized results in the 12/130 Er-Yb codoped fiber. By polarization-division multiplexing 32 replicas, transform-limited pulse with 126-fs duration, 20.3-nJ pulse energy, and 80-MHz repetition rate was generated from a few-mode Er-Yb codoped fiber. Furthermore, limitations on the coherent combining efficiency are discussed.